Recent Export Credit Market Developments. (IMF Working Papers; Working Paper ;, 1997)
Export credit agencies (ECAs) have played a critical role in financing for developing countries in recent years, and officially supported export credits have been growing in volume. The current export credit exposure to developing countries and economies in transition has reached almost half a trillion dollars. This paper reviews developments in export credit markets affecting exposure, new commitments, and cover policy for developing countries and economies in transition and discusses three key issues affecting export credit markets: a more widespread involvement of ECAs in project financing transactions, a strong presence of ECAs in the market for investment insurance, and a deepening of the forfeiting market.